2002
DOI: 10.1103/physrevd.65.064014
|View full text |Cite
|
Sign up to set email alerts
|

Thick brane worlds and their stability

Abstract: Three types of thick branes, i.e., Poincaré, de Sitter and Anti-de Sitter brane are considered. They are realized as the non-singular solutions of the Einstein equations with the non-trivial dilatons and the potentials. The scalar perturbations of these systems are also investigated. We find that the effective potentials of the master equations of the scalar perturbations are positive definite and consequently these systems are stable under the small perturbations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
219
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(226 citation statements)
references
References 45 publications
6
219
1
Order By: Relevance
“…A massive scalar field in the bulk was first introduced by Goldberger and Wise [10] to stabilize the brane separation in RSI. The RS model with a minimally coupled scalar field in the bulk, referred to as the thick brane model, has been constructed for maximally symmetric solutions on the brane [11]. It has been demonstrated that the bulk scalar potential and the corresponding brane potential can be derived from a superpotential in which case the solution of the static vacuum geometry reduces to a set of first-order BPS-like equations [12].…”
Section: Introductionmentioning
confidence: 99%
“…A massive scalar field in the bulk was first introduced by Goldberger and Wise [10] to stabilize the brane separation in RSI. The RS model with a minimally coupled scalar field in the bulk, referred to as the thick brane model, has been constructed for maximally symmetric solutions on the brane [11]. It has been demonstrated that the bulk scalar potential and the corresponding brane potential can be derived from a superpotential in which case the solution of the static vacuum geometry reduces to a set of first-order BPS-like equations [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, one can expect that quantum bulk gravity may be important in the realization of warped compactification within the AdS/CFT scheme or in improving the Randall-Sundrum scenario. As a toy model for quantum bulk gravity one can consider a quantum bulk scalar [9][10][11][12].…”
mentioning
confidence: 99%
“…There are a number of well known exact solutions which belong to this class of models (e.g. [8,12,17,24,25,26,27,28]). We investigated stability of some of these models under the conformal excitations which are functions of 4-D space-time.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was observed that inclusion of matter can stabilize radions for different types of branes. It can be done with the help of bulk scalar field [9], [15]- [17], perfect fluid on branes [18] and the Casimir effect between branes [19,20].…”
Section: Introductionmentioning
confidence: 99%